2005
DOI: 10.1093/jpepsy/jsj090
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Adherence and Metabolic Control in Urban Youth with Poorly Controlled Type 1 Diabetes: The Mediating Role of Mental Health Symptoms

Abstract: Results suggest that gender differences in adherence may be attributed, in part, to gender differences in externalizing symptoms in urban youth with poor metabolic control. Interventions targeting these symptoms may be necessary to improve adherence and HbA1C in both boys and girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 40 publications
6
62
2
1
Order By: Relevance
“…If sample sizes differed for different measures, we used the measures that had a larger sample size (10,11). One study reported both selfreported and caregiver reported data for depression and self-care; we used selfreported data for the analysis (12). Where two papers were published from samples that were not independent, we included the article with the stronger design: longitudinal over cross-sectional (13,14) or larger sample (15,16).…”
Section: Study Proceduresmentioning
confidence: 99%
“…If sample sizes differed for different measures, we used the measures that had a larger sample size (10,11). One study reported both selfreported and caregiver reported data for depression and self-care; we used selfreported data for the analysis (12). Where two papers were published from samples that were not independent, we included the article with the stronger design: longitudinal over cross-sectional (13,14) or larger sample (15,16).…”
Section: Study Proceduresmentioning
confidence: 99%
“…Results of a population based study by Kanton et al suggest that independent factors are associated with higher chance of meeting criteria for major depression. The criteria for developing major depression are younger age, smoking, and female, less education, unmarried, with BMI 30. In men major depression was found to be a result of similar factors including higher number of of diabetic complications.…”
Section: Clinical Diabetic Depression and Sociological Involvementmentioning
confidence: 96%
“…Findings in 1,223 adults with diabetes-depression suggest that depression symptoms make it harder to reach optimal A1c levels, but anti-depressive treatment may ameliorate this effect [29]. Studies report a clear link between mental health symptoms and poor metabolic control (high levels of HbA1c) without gender differences in youths with poorly controlled type I diabetes [30]. Also, unlike blood pressure, depression seems to make it harder to obtain the target values for lipids [29].…”
Section: Setting Clinical Goals For Depressed Diabetic Patientsmentioning
confidence: 99%
“…[20][21][22] In particular, there is evidence that symptoms of depression and anxiety may disrupt adherence through decreased concentration, impact on judgment ability, memory impairment, and decreased motivation and energy, which are all symptoms of the disorders themselves. [23][24][25] Additional psychological characteristics that have been found to be related to diabetes adherence and subsequent glycemic control are maladaptive eating attitudes and behaviors, including the potential for insulin omission for the purposes of weight control.…”
Section: Individualmentioning
confidence: 99%